Intensified Northern Hemisphere Glaciation Facilitates Continuous Accumulation of Late Pliocene Loess on the Western Margin of the Pamir. Issue 16 (18th August 2022) - Zan, Jinbo; Ning, Wenxiao; Heller, Friedrich; Fang, Xiaomin; Zhang, Weilin; Kang, Jian
Abstract: Thick eolian loess sequences in arid Central Asia (CA) contain a wealth of information on the intensity variations of midlatitude westerlies and the aridification history of the nearby deserts. In this study, detailed lithologic and magnetostratigraphic investigations suggest that loess deposits on the western margin of the Pamir Plateau began to accumulate at around 2.7 Ma, representing the most complete and oldest loess‐paleosol sequence in western CA. The widely distributed continuous loess deposition in the region suggests a rapid desiccation of CA during the late Pliocene. A synthesis of the initial timing and spatial distribution of late Cenozoic eolian deposits on the Eurasian continent further demonstrates that the dramatic increase in global ice volume exerted a dominant role in the expansion of eolian loess deposits in CA, China, and Europe, and middle Pleistocene expansion is a crucial precondition for the establishment of modern distribution patterns of the Eurasian loess belt. Plain Language Summary: To understand when and how the Asian inland aridification formed and evolved is of great significance in understanding the earth's climatic system. Continuous accumulation of eolian loess sediments in CA contains a wealth of information on dry land evolution and the formation of nearby deserts. To date, however, late Pliocene and early Pleistocene loess deposits in CA have rarely been reported, hindering our understanding of the aridification history of Asian interior. Detailed lithologic and magnetostratigraphic investigations suggest that continuous loess deposition occurred in southern Tajikistan since around 2.7 Myr, indicating a rapid desiccation of CA during the late Pliocene. Further synthesis of the timing of the initial appearance of Cenozoic eolian deposits on the Eurasian continent demonstrates that global cooling and the stepwise expansion of eolian dust delivery in Eurasia are tightly connected. These results provide new insights into the links between the uplift of the Pamir‐Tian Shan region, global cooling and the Central Asian interior climate since the late Cenozoic. Key Points: Loess deposits on the western margin of the Pamir began to accumulate at around 2.7 Ma Intensified glaciation facilitates continuous accumulation of the loess deposits in Central Asia Middle Pleistocene expansion of loess is a crucial precondition for the establishment of modern distribution patterns of Eurasian loess